PEMBELAJARAN MEMPRODUKSI TEKS EKSPOSISI DENGAN MENGGUNAKAN METODE PROBLEM BASED LEARNING - Deni Iskandar; Mochamad Irfan Taofik; Indra Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The learning title produces exposition texts by using problem based learning method in class X T KR students. As for the background of the problem that not all students can understand especially to present their ideas related to what is taught in Indonesian language subjects. Background problem there are 3 points: Is the Problem Based Learning method can improve the ability of writing exposition text ?, Is the method of learning problem-based effective learning used in learning writing exposition text ?, is there a difference before and after using the method of problem based learning on X? The research design used by researchers is One-Group Pretest-Postest Design. Where this design is preted before treatment and postes after treatment. Thus the treatment results can be known more accurately, because it can compare test results between before and after treatment. The population of SMK BINA PEMUDA is less than 150 people and the sample of the research is 20 students with 18 men and 2 women. The result of the research before using the method is seen from the average value of the initial test of 47.75 and the mean value of the final test 57 with the mean of 9,25 and the value of t table = 1, 70 turns t count> t table (7.64> 1.70), which means that the interruption between the initial test and the final test increased significantly.